Postantibiotic and Sub-MIC Effects of Exebacase (Lysin CF-301) Enhance Antimicrobial Activity against Staphylococcus aureus - Oh, Jun Taek (Antimicrob Agents Chemother, 2019)
CF-301 (exebacase) is a recombinantly produced bacteriophage-derived lysin (cell wall hydrolase) and is the first agent of this class to enter clinical development in the United States for treating bacteremia including endocarditis due to Staphylococcus aureus. Whereas rapid bactericidal activity is the hallmark in vitro and in vivo response to CF-301 at exposures higher than the MIC, prolonged antimicrobial activity, mediated by cell wall damage, is predicted at concentrations less than the MIC. In the current study, a series of in vitro pharmacodynamic parameters, including the postantibiotic effect (PAE), postantibiotic sub-MIC effect (PA-SME), and sub-MIC effect (SME), were studied to determine how short-duration and sub-MIC CF-301 exposures affect the growth of surviving staphylococci and extend its antimicrobial activity. Mean PAE, PA-SME, and SME values up to 4.8, 9.3, and 9.8 h, respectively, were observed against 14 staphylococcal strains tested in human serum; growth delays were extended by 6 h in the presence of daptomycin. Exposures to CF-301 at sub-MIC levels as low as 0.001× to 0.01× MIC (∼1 to 10 ng/ml) resulted in aberrant cell wall ultrastructure, increased membrane permeability, dissipation of membrane potential, and inhibition of virulence phenotypes, including agglutination and biofilm formation. A mouse thigh infection model designed to study the PAE was used to confirm our findings and demonstrate in vivo growth delays of ≥19.3 h. Our findings suggest that at CF-301 concentrations less than the MIC during therapeutic use, sustained reductions in bacterial fitness and virulence may substantially enhance efficacy.